Modelling dust around Nearby Evolved Stars Survey (NESS) Targets. Issue Volume 14:Issue S343(2019) (August 2018) - Srinivasan, Sundar; Dharmawardena, T.; Kemper, F.; Scicluna, P.
Abstract: We present radiative transfer modelling of the dust around U Ant, a well-studied detached-shell source. U Ant is among the >400 sources targeted by the Nearby Evolved Stars Survey (NESS; PI: P. Scicluna), and the procedure used to model this source will be applied to the rest of the AGB sample in NESS.